Espaço maker em bibliotecas: Um ambiente dinâmico e criativo - Vital, Stefanne Martins (FIC - Faculdade de Informação e Comunicação, 2022)
In the scenario of a lot of information, it is expected that all services will be readapted to better serve them, being a library that makes this reading of services indispensable. Which presents the existence of exclusive spaces for its libraries, which offers exclusive services to open and offers exclusive resources to generate and learn for users with all the spaces and resources to offer resources. Libraries from the continents were selected: European, Asian, African, Oceania and America, for the realization of a given typology, spaces for creation and tools available to their users. In the writing of the work it was possible to understand the service management libraries that make room for the inclusion of activities and tools of the maker and maker movement.